Polyamine Function in Plants: Metabolism, Regulation on Development, and Roles in Abiotic Stress Responses - Chen, Dandan; Shao, Qingsong; Yin, Lianghong; Younis, Adnan; Zheng, Bingsong (Frontiers in Plant Science, 2019)
Polyamines (PAs) are low molecular weight aliphatic nitrogenous bases containing two or more amino groups. They are produced by organisms during metabolism and are present in almost all cells. Because they play important roles in diverse plant growth and developmental processes and in environmental stress responses, they are considered as a new kind of plant biostimulant. With the development of molecular biotechnology techniques, there is increasing evidence that PAs, whether applied exogenously or produced endogenously via genetic engineering, can positively affect plant growth, productivity, and stress tolerance. However, it is still not fully understood how PAs regulate plant growth and stress responses. In this review, we attempt to cover these information gaps and provide a comprehensive and critical assessment of the published literature on the relationships between PAs and plant flowering, embryo development, senescence, and responses to several (mainly abiotic) stresses. The aim of this review is to summarize how PAs improve plants’ productivity, and to provide a basis for future research on the mechanism of action of PAs in plant growth and development. Future perspectives for PA research are also suggested.